Malnutrition inflammation in chronic kidney disease undergoing hemodialysis in Cipto Mangunkusumo Hospital - Adrianto, Yudhi; Utari, Diah M (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2024)
Background: Malnutrition was a nutritional problem in hemodialysis with prevalence 50-70% and 2018 study at Cipto Mangunkusumo Hospital showed the prevalence was 39%.Objectives: This study was team study of Renal and Hypertension Unit RSCM, using cross sectional design, primary data collected in February and May 2018.Materials and Methods: The sample size used a hypothesis test with total sample of 120 patients. Data obtained through interviews and laboratory data obtained through medical records. Univariate, bivariate and multivariate analysis were carried out to see the determinant factors that influence the Malnutrition Inflammation Score (MIS).Results: The results showed that there were relationship between sex (p<0.022), age (p<0.031), etiology chronic kidney disease (p<0.037), duration hemodialysis (p<0.025), protein intake (p<0.030) and grip strength (p<0.010). The determinant factors significantly associated with MIS were sex p<0.0001, age p<0.014, protein intake p<0.018, and grip strength p<0.017.Conclusion: The conclusions of this study were the prevalence of inflammatory malnutrition in hemodialysis patients was 55.8%, male had risk of 4.1 malnutrition, age ≥40 years had risk of 3.1, inadequate protein intake had risk 2.8 times malnutrition and less grip strength as a protective variable had a 0.23 times lower risk.Keywords : Chronic kidney disease; hemodialysis; malnutrition inflammation; nutritional status